Financing investments in a landlord port - Carolyn Somorowsky; Hans-Dietrich Haasis (Data Science in Maritime and City Logistics: Data-driven Solutions for Logistics and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 30, 2020)
Purpose: Given of a landlord port model, private operating companies have to invest in superstructure, equipment and labor to maintain and improve the physical and non-physical flow of goods. The purpose of this paper is to examine interdependencies as well as existing collaborative strategies between operators in ports and to develop a collaborative concept for financing such investments. Methodology: A literature review on supply chain management, port and collaboration is applied with a focus on vertical inter-organizational integration and collaborative strategies of financing investments. Based on the idea of cooperative game theory, a new collaborative concept for financing investments in ports is developed. Findings: In literature, collaboration and the supply chain perspective are gaining in importance. However, collaborative approaches for financing investments that are necessary for the improvement of the value chain are almost completely left out of consideration. Originality: Academic literature on network structures in ports as well as vertical inter-organizational integration is limited. This paper emphasizes the importance of collaboration in port structures and in a first attempt, discusses how joint financing provides added value for the logistics chain.
urn:nbn:de:gbv:830-882.0115596; hdl:10419/228915; https://econpapers.repec.org/RePEc:zbw:hiclpr:30
Keywords: 650; Logistics; Industry 4.0; Supply Chain Management; Sustainability; City Logistics; Maritime Logistics; Data Science